The sanction for breaching the promise of the contract in view of the amendment of the French Civil Code by Decree No. 131 of 2016 - Abdullah, Ahmed; Mutashar, Ali (Journal of Legal Sciences, 2022)
Breach of the promise to contract and the penalty resulting from this breach is one of the important topics that occupied a wide space of interest in civil law jurisprudence when studying the subject of the promise to contract, and this importance did not disappear from the mind of the judiciary, so it was present in its decisions. This importance is due to the specificity of the promise to contract, despite being a contract Like other contracts, the breach of it is characterized by a special nature, as it may take place before the stage of expressing the desire on the part of the one who is promised, and it may be after expressing that desire. Based on this importance, the penalty for breaching the contract promise will be the subject of this research.